Mycorrhizal helper bacteria further promote mycorrhizal fungi to improve cold tolerance in rice seedlings: evidence from oxidative stress, osmoregulation, photosynthesis, and related genes in rice - Shi, Feng; Liu, Fangyuan; He, Xue; Zhu, Siyu; Li, Honghe; Ding, Yiwen; Zhang, Bo; Xu, Tianle; Song, Fuqiang (Frontiers in Plant Science, 2025)
IntroductionCold stress critically threatens rice productivity, necessitating innovative strategies to enhance seedling resilience. While arbuscular mycorrhizal fungi (AMF) and associated bacteria synergistically improve plant stress tolerance, their collaborative mechanisms in rice cold adaptation remain underexplored. MethodsHere, we developed a composite inoculant combining Rhizophagus intraradices (Ri) with Agrobacterium rhizogenes (Ar) and Bacillus subtilis (Bs) to investigate their synergistic effects under graded cold stress (25–4 °C). ResultsThe Ri+Ar+Bs (RAB) consortium elevated mycorrhizal colonization by 17% (reaching 87.5%) and synergistically promoted plant growth, increasing height and root length by 9.56% and 43.7%, respectively, under 4 °C stress compared to Ri alone. RAB enhanced antioxidant capacity (24.9% higher SOD activity, 12.37-fold CAT activity) and proline accumulation (78.4%), reducing malondialdehyde (43.7%) and electrolyte leakage (13.64%). Hormonal equilibrium was maintained via upregulated indole-3-acetic acid and gibberellic acid levels. Photosynthetic performance improved significantly (11.29% higher net rate at 4 °C), supported by activation of OsHBP1b and CBF1. Concurrently, RAB upregulated cold-tolerance genes (LTG5RT, OsDREB1A), with functional specialization observed.DiscussionAr amplified Ri-mediated height improvement and gene expression, while Bs enhanced root development and photosynthetic efficiency. These findings advance microbial consortia design for climate-resilient agriculture, offering actionable strategies to safeguard rice productivity under extreme cold.